2005
DOI: 10.1016/j.jasms.2005.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray ionization (ESI) tandem mass spectrometric analysis of meso-tetrakis(heptafluoropropyl)porphyrin

Abstract: The results of an electrospray ionization (ESI(ϩ) and ESI(Ϫ)) collision-induced fragmentation investigation of meso-tetrakis(heptafluoropropyl)porphyrin (T F HP) are reported. The fragmentation patterns of T F HP show, in both ionization modes, the formation of fragments with direct covalent meso-alkyl-to-␤-linkages on elimination of HF. In addition, in the ESI(ϩ) mode, the losses of perfluoroalkyl radicals are observed. A detailed analysis of the fragmentation patterns allows conclusions to be drawn on the id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
4
8
0
Order By: Relevance
“…Further, as the loss of aryl radical fragments demonstrates, radical pathways also cannot be excluded. In fact, we have observed the HF-elimination in meso-heptafluoropropyl-substituted porphyrins under ESI conditions that is, under ESI(ϩ) conditions, intermingled with a radical fragmentation pathway of the meso-alkyl groups [35].…”
Section: F Pp ϫ H]mentioning
confidence: 90%
See 1 more Smart Citation
“…Further, as the loss of aryl radical fragments demonstrates, radical pathways also cannot be excluded. In fact, we have observed the HF-elimination in meso-heptafluoropropyl-substituted porphyrins under ESI conditions that is, under ESI(ϩ) conditions, intermingled with a radical fragmentation pathway of the meso-alkyl groups [35].…”
Section: F Pp ϫ H]mentioning
confidence: 90%
“…Electrospray ionization (ESI) mass spectrometry (MS) is becoming a popular technique for the analyses of porphyrins [25][26][27][28][29][30][31][32][33][34][35].…”
mentioning
confidence: 99%
“…In the case of the loss of H 2 , a similar cyclization with elimination of an HF molecule and formation of a fivemembered ring was described for pyrrolidine-fused cationic°chlorins°and°isobacteriochlorins° [22],°and°for meso-tetrakis(heptafluoropropyl)porphyrin° [13]. …”
Section: ]mentioning
confidence: 78%
“…In particular, the Herpes simplex virus is one of the most common agents responsible for viral infections in man [5]. From preliminary virus inactivation studies carried out with Herpes simplex virus type 1 (HSV-1) using the cationic porphyrins 1 and 2 (Scheme 1), we have observed that despite their structural resemblance and their similar photocytotoxicity profiles, Compound 1 was very effective in the photoinactivation of the virus, whereas Compound 2 displayed no virucidal effect in the same conditions [6].Electrospray ionization mass spectrometry (ESI-MS) was successfully applied to characterize porphyrins as early as 1991 [7] and both ESI-MS [8 -11] and tandem mass spectrometry (ESI-MS/MS) [12,13] have been used to study neutral and cationic porphyrins since then. We wanted to know if the two porphyrin isomers, 1 and 2, could be differentiated by ESI-MS/MS and if the informa-…”
mentioning
confidence: 99%
See 1 more Smart Citation